Step-by-step acquisition of the gibberellin-DELLA growth-regulatory mechanism during land-plant evolution. - Yasumura, Y; Crumpton-Taylor, M; Fuentes, S; Harberd, N (2007)
Angiosperms (flowering plants) evolved relatively recently and are substantially diverged from early land plants (bryophytes, lycophytes, and others [1]). The phytohormone gibberellin (GA) adaptively regulates angiosperm growth via the GA-DELLA signaling mechanism [2-7]. GA binds to GA receptors (GID1s), thus stimulating interactions between GID1s and the growth-repressing DELLAs [8-12]. Subsequent 26S proteasome-mediated destruction of the DELLAs promotes growth [13-17]. Here we outline the evolution of the GA-DELLA mechanism. We show that the interaction between GID1 and DELLA components from Selaginella kraussiana (a lycophyte) is GA stimulated. In contrast, GID1-like (GLP1) and DELLA components from Physcomitrella patens (a bryophyte) do not interact, suggesting that GA-stimulated GID1-DELLA interactions arose in the land-plant lineage after the bryophyte divergence ( approximately 430 million years ago [1]). We further show that a DELLA-deficient P. patens mutant strain lacks the derepressed growth characteristic of DELLA-deficient angiosperms, and that both S. kraussiana and P. patens lack detectable growth responses to GA. These observations indicate that early land-plant DELLAs do not repress growth in situ. However, S. kraussiana and P. patens DELLAs function as growth-repressors when expressed in the angiosperm Arabidopsis thaliana. We conclude that the GA-DELLA growth-regulatory mechanism arose during land-plant evolution and via independent stepwise recruitment of GA-stimulated GID1-DELLA interaction and DELLA growth-repression functions.